Penerapan Bisnis Digital untuk Pemasaran Gurita Bakar di Pasar Malam - Rendy Andika; Riky Apriadi; Syahadatillah Syahadatillah; Tata Sutabri (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Night markets have long been a popular place to do food business, and one of the trending products is grilled octopus. To optimize this business potential, implementing a digital business strategy has become key. This journal presents a brief overview of how digital business is used to market grilled octopus at night markets. The application of digital business in marketing grilled octopus at night markets involves various aspects. First of all, outlet owners can take advantage of technology by creating an official website for their outlet. This website not only serves as a platform to display menus and store locations, but also as a tool to communicate with potential customers. Social media also plays an important role in marketing. By managing accounts on platforms such as Facebook, Instagram, and Twitter, outlet owners can share product images, customer reviews, and promotional information. Apart from that, email marketing is also an effective strategy. Collecting customer email addresses and sending them information about special offers, discounts, or new menu items can increase customer engagement. Joining popular food delivery apps such as GrabFood or GoFood also helps in expanding customer reach, especially if the grilled octopus outlet does not yet have a physical presence in the location. Although implementing a digital business has clear benefits, there are also challenges that need to be overcome. Intense competition in night markets requires outlet owners to create creative and different marketing. Additionally, adequate online management is the key to success, and outlet owners may need to train themselves or obtain technical support to manage their digital assets. In conclusion, the implementation of digital business has had a positive impact in marketing grilled octopus at night markets. However, outlet owners need to be aware of the challenges that may arise and try to continue to improve their strategies in facing increasingly fierce competition in the digital world.